TOP-ID: a Delphi technique-guided development of a prescription and deprescription tool for adults with intellectual disabilities. Issue 11 (4th November 2020) - Lonchampt, Sophie; Gerber, Fabienne; Aubry, Jean-Michel; Desmeules, Jules; Besson, Marie; Markus, Kosel
Abstract : Objectives: Adults with an intellectual disability (AWID) are often polymedicated because of somatic and psychiatric health problems. Besides, they may display challenging behaviours, leading to off-label prescription of psychotropic drugs, without efficacy and with numerous adverse effects. In this context, a prescription/deprescription tool (Tool for Optimising Prescription in Intellectual Disability/TOP-ID) was developed to improve the care of AWID. This paper describes how TOP-ID was designed. Design: Four-step consensus-based process involving a review of the literature, eight semistructured interviews and a two-round Delphi process. Setting: Seventeen general practices and university and general hospitals from Belgium, France and Switzerland. Participants: Eighteen French-speaking physicians from different domains of expertise participated in the Delphi process. Primary and secondary outcome measures: For the Delphi iteration process, consensus was defined as at least a 65% agreement between the experts. Results: Two rounds were needed for the Delphi process. Eighty-one items of the tool were submitted to 18 out of 35 recruited French-speaking experts during the first round. Sixty-nine per cent of the items reached a rate of agreement of 65% or more in that round. Thirteen questions were reformulated and resubmitted for the second Delphi iteration round. All of the statements reached a rate of agreement of 65% or more in the second round. Conclusion: TOP-ID is the first prescription–deprescription tool developed specifically for AWIDs in French. It is intended to help prescribers document patient care in order to reduce prescription errors and to improve safety. The next steps of the project include the development of an electronic version of TOP-ID and a utility study.